The interfacial structure underpinning the Al-Ga liquid metal embrittlement: disorder vs. order gradients. (November 2021) - Shen, Min; Li, Yanwen; Hu, Chongze; Xue, Sikang; Xiang, Congying; Luo, Jian; Yu, Zhiyang
Abstract: Embrittlement of polycrystalline aluminum by liquid gallium represents a classic example of liquid metal embrittlement, whereas the interfacial atomic structure of Ga penetration front remains elusive despite decades of investigation. We performed aberration-corrected scanning transmission electron microscopy characterization to uncover the atomistic structure of Ga-enriched complexion within Al general grain boundaries. Multiple-layer adsorption of Ga with ordering gradients is revealed, consisting of disordered Ga layers at the GB core that are sandwiched by two more ordered adsorbate layers connecting to both aluminum grains. The ordering gradients within the interfacial complexion are further verified by the hybrid Monte Carlo and molecular dynamic simulations. This study advances our fundamental understandings of complexion structures within general grain boundaries. Graphical abstract: Image, graphical abstract